Match demands on officials and umpires across variations of lacrosse - Ripley, N. J.; Fahey, J. T.; Quinn, M. E. (International Journal of Performance Analysis in Sport, 2026)
The physical demands on lacrosse officials throughout different variants of the game remain largely unknown. The purpose of this study was to quantify the match demands of officials in field lacrosse (FL), box lacrosse (BL) and sixes lacrosse (SL). Thirty officials (10 Females and 20 Males; 34.3 ± 8.2 years, 168.4 ± 13.2 cm, 73.4 ± 6.8 kg) were monitored during 96 competitive matches (33 FL matches, 39 SL matches and 24 BL matches) using 10 hz GPS microtechnology. Significant differences (p < 0.001, Eta2>0.11) in physical demands were observed, with trivial to very large differences (d = 0.19-6.99) identified between different lacrosse variants. There was a moderate difference (p = 0.01, Eta2 = 0.05) between quarters and variations. FL officials covered the greatest low intensity distances (<=5.5 m/s), while SL officials exhibited greater high-speed running (>5.5 m/s). BL and SL, both smaller variants, resulted in more frequent accelerations and decelerations in comparison to FL. These findings highlight that officials experience unique physical challenges depending on the variant, emphasising the need for tailored physical preparation strategies for each format, particularly for those aiming to officiate at the highest levels of competition.